ILMU TAJWID PERSPEKTIF FILSAFAT ILMU: KAJIAN ONTOLOGI, EPISTEMOLOGI, DAN AKSIOLOGI - Rahmah, Sofia Laila; Rohanda, Rohanda; Kodir, Abdul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2025)
Tajwid is a discipline that explores the methods of reciting the Qur'an correctly according to established rules. This study aims to explore the essence of Tajwid through ontological, epistemological, and axiological approaches, as well as analyze its significance in the lives of Muslims, encompassing spiritual, social, and educational aspects. This research employed a qualitative method with a literature study approach, examining various authoritative sources in Tajwid, including classical texts and direct instruction from competent teachers. The findings indicate that Tajwid is not merely a technique for reciting the Qur'an, but also possesses a profound spiritual dimension, serving as a means of drawing closer to Allah SWT. Tajwid is learned through diverse sources, with the implementation of varied learning methods, both face-to-face and through online platforms. Although technology has facilitated access to Tajwid learning, this study reveals that the main challenge faced is a lack of public awareness regarding the urgency of Tajwid in worship. Tajwid has an essential role in the life of a Muslim, both from a spiritual perspective and in preserving the tradition of reciting the Qur'an correctly. Therefore, enhancing the understanding and practice of Tajwid is imperative in order to maintain the authenticity of the meaning of the Qur'an and optimize the quality of worship for Muslims.